Depression severity moderates the relation between self-distancing and features of emotion unfolding. (1st March 2018) - Résibois, Maxime; Kuppens, Peter; Van Mechelen, Iven; Fossati, Philippe; Verduyn, Philippe
Abstract: Thinking about a negative event from a self-distanced (vs. self-immersed) perspective is associated with lower emotion intensity. However, it is unclear how self-distancing impacts emotion unfolding and whether individual differences in depression severity moderate this impact. We addressed this issue by examining the effect of self-distancing on emotion explosiveness (i.e., steepness of the emotion response at onset) and accumulation (i.e., intensification of the response after onset) in participants differing in levels of depression. Participants adopted a self-immersed or self-distanced perspective while reading and thinking about manipulated negative social feedback. Both explosiveness and accumulation decreased when participants adopted a self-distanced perspective. Moreover, the effect of perspective taking on accumulation was especially outspoken for people with high levels of depression severity. Highlights: Perspective taking impacted both emotion explosiveness and accumulation. Its impact on explosiveness is similar for people high and low in depression severity. Its impact on accumulation is more outspoken for people high in depression severity.